2008
DOI: 10.1002/cite.200800056
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen von Filmströmungen mittels eines neuartigen Micro Particle Image Velocimetry Messverfahrens

Abstract: Der Wärme‐ und Stoffübergang in Packungskolonnen wird erheblich durch die komplexe Fluiddynamik der flüssigen Phase beeinflusst, für deren tiefergehendes Verständnis zwingend Informationen über das Geschwindigkeitsfeld benötigt werden. Zu diesem Zweck wurde eine neue μPIV (Micro Particle Image Velocimetry)‐Messmethode entwickelt, bei der das Geschwindigkeitsprofil durch die bewegte wellige Oberfläche gemessen wird, sodass erstmalig Analysen auf nicht transparenten Packungsmaterialien ermöglicht werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 17 publications
0
15
0
2
Order By: Relevance
“…The CFD simulations were compared with PIV measurements, using a lPIV [36]. Simulations and experiments showed the same structure of the macroscopic flow.…”
Section: Flow Fieldmentioning
confidence: 98%
“…The CFD simulations were compared with PIV measurements, using a lPIV [36]. Simulations and experiments showed the same structure of the macroscopic flow.…”
Section: Flow Fieldmentioning
confidence: 98%
“…The relatively macroscopic experiment concentrates the research on the whole plate, where the global parameters such as the wetted area of the plate, liquid thickness, and liquid surface velocity along the flow direction are measured and analyzed; 30 the relatively microscopic experiment focuses the research on a small region on the plate, where the local parameters such as the velocity profile along the liquid thickness are scanned and investigated layer-by-layer. 31 Figure 4 shows the experimental setups for the case without the countercurrent gas flow. Figure 4a displays the microscopic experimental setup and Figure 4b shows the macroscopic experimental setup.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental investigations using optical measurements showed that the Nußelt theory is valid for inclined smooth plates at low Reynolds numbers 13, 15. true δnormalL = 3 V · normalL νnormalL Bgsinα 3 …”
Section: Concept Of the Flexible Wetted‐wall Columnmentioning
confidence: 99%